2015
DOI: 10.1016/j.juro.2015.04.106
|View full text |Cite
|
Sign up to set email alerts
|

The Artificial Urinary Sphincter is Superior to a Secondary Transobturator Male Sling in Cases of a Primary Sling Failure

Abstract: In this cohort of patients with post-prostatectomy stress urinary incontinence and a failed primary sling those who underwent a secondary sling procedure were up to 6 times more likely to have persistent incontinence vs those who underwent artificial urinary sphincter placement. These data are useful for counseling patients and planning surgery. We currently recommend placement of an artificial urinary sphincter for patients in whom an initial sling has failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…32 In a case series of 61 men after a failed primary male sling procedure, continence was higher with placement of an AUS, rather than by a secondary sling procedure (treatment failure of 6% and 55%, respectively). 33 We demonstrated that institutional caseload is associated to dry rate and surgical revision. A median ICL above 39 and 42 is a protective factor in terms of dry rate and surgical revision respectively.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…32 In a case series of 61 men after a failed primary male sling procedure, continence was higher with placement of an AUS, rather than by a secondary sling procedure (treatment failure of 6% and 55%, respectively). 33 We demonstrated that institutional caseload is associated to dry rate and surgical revision. A median ICL above 39 and 42 is a protective factor in terms of dry rate and surgical revision respectively.…”
Section: Discussionmentioning
confidence: 77%
“…In a small prospective case series assessing clinical results of AUS placement after failure of male sling surgery, mid‐term results evidenced that results of this procedure are comparable to first‐line AUS implantation in terms of continence (87%) and complications (17%) . In a case series of 61 men after a failed primary male sling procedure, continence was higher with placement of an AUS, rather than by a secondary sling procedure (treatment failure of 6% and 55%, respectively) …”
Section: Discussionmentioning
confidence: 97%
“…There is some evidence to consider that AUS placement is superior to a secondary transobturator male sling after primary sling failure [19], but randomized trials for this specific indication are lacking. On the other hand, recurrent or persistent SUI after AUS may result from different scenarios leading to explant in 1 out of 5 devices in the short term [20].…”
Section: Discussionmentioning
confidence: 99%
“…Early and mild degrees of SUI after prostate surgery may be improved by intensive pelvic floor muscle training and life style modifications but when conservative therapy options fail, surgical treatment is recommended . The artificial urinary sphincter (AUS), by far the most frequently implanted device worldwide, is the established ‘gold standard’ in severe UI and is superior to a secondary male sling as reported in the literature . Yet the last few years have been marked by a rapid development of various adjustable or non‐adjustable sling systems of different designs to treat milder forms of SUI without any mechanical components that need to be de‐activated or activated by the patient himself .…”
Section: Introductionmentioning
confidence: 99%